2016
DOI: 10.1063/1.4943379
|View full text |Cite
|
Sign up to set email alerts
|

Free carrier generation and recombination in PbS quantum dot solar cells

Abstract: Time Delayed Collection Field (TDCF) and Bias Assisted Charge Extraction (BACE) experiments are used to investigate the charge carrier dynamics in PbS colloidal quantum dot solar cells. We find that free charge carrier creation is slightly field dependent, thus providing an upper limit to the fill factor. BACE measurements reveal a rather high effective mobility of 2 × 10 cm²/Vs, meaning that charge extraction is efficient. On the other hand, a rather high steady state non-geminate recombination coefficient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…voltage (Figure 4a) shows only a minor decrease for increased active layer thickness which originates from a higher recombination, 36 yet does not strongly influence the optimal thickness for the maximum PCE (Figure 4d). It is interesting to compare the optimal thickness of the CsMAFA-…”
Section: Results and Disscussionmentioning
confidence: 98%
See 1 more Smart Citation
“…voltage (Figure 4a) shows only a minor decrease for increased active layer thickness which originates from a higher recombination, 36 yet does not strongly influence the optimal thickness for the maximum PCE (Figure 4d). It is interesting to compare the optimal thickness of the CsMAFA-…”
Section: Results and Disscussionmentioning
confidence: 98%
“…A further increase of the thickness drastically reduces the charge extraction, meaning that the charge carriers recombine prior to extraction due to the longer distance they must overcome before reaching the extraction layers. We note that the open-circuit voltage (Figure a) shows only a minor decrease for increased active layer thickness which originates from higher recombination yet does not strongly influence the optimal thickness for the maximum PCE (Figure d). It is interesting to compare the optimal thickness of the CsMAFA–PbS devices to that of the reference devices: 250 and 325 nm for MAPbI 3 –PbS and PbX 2 –PbS devices, respectively. , Yang et al reported that the short carrier diffusion length within the MAPbI 3 –PbS active layer is responsible for the decrease in photovoltaic performance for thicknesses above 250 nm .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The much more pronounced initial recombination loss in the thin sample is, therefore, clearly revealed by the dependence of Q tot on fluence at even short delays. As attempts to fit these traces with the established iterative approach 25 33 , using a constant, time independent recombination coefficient, turned out to be unsuccessful, We therefore analyzed these data with a new approach as outlined in refs 35 and 36 . In short, the incremental change of the total extracted charge density per time increment, Δ n tot /Δ t , with n tot = Q tot ( eAd ), is plotted versus n coll = Q coll ( eAd ) for different delay times and fluences.…”
Section: Resultsmentioning
confidence: 99%
“…After a given delay time, the carriers which survived recombination are extracted from the device by applying a reverse bias V coll . The technique has been used in the past to study free charge generation and recombination in organic, [34] inorganic [47] and hybrid devices. [48] A fluence series is shown in Figure 2D (see Figures S5 and S6 (Supporting Information) for additional data).…”
Section: Transient Absorption and Charge Extractionmentioning
confidence: 99%